Gambaran Perkembangan Kognitif Pada Anak Autisme: Description of Cognitive Development in Autistic Children - Aka Watrina Anindita; Aratsa Nurhayati; Rizky Raudhatul Jannah; Naeila Rifatil Muna (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
Children's cognitive development is a thinking process that allows their brains to recognize, know, understand and reason so that they can understand material more easily. However, for children with special needs, there are certainly slight differences in cognitive development from children in general. Autism is a condition where individuals are more interested in their own world and tend not to want to interact socially with the people around them. This study aims to collect information about the cognitive development of 6 year old autistic children. This research uses a qualitative descriptive approach with a sample of one autistic child who attends Kindergarten "X" Cirebon City. Research data was obtained from observations and interviews. The research results show that the cognitive development of children with autism is indeed less than that of other children. The cognitive development of autistic children aged 6 years is different, especially in the way they learn, think and solve problems. Therefore, early intervention is very important which must be carried out by parents and teachers. Therefore, it is important for parents and teachers to create a learning environment that is supportive and appropriate to children's needs.   ABSTRAK Perkembangan kognitif anak-anak adalah proses berpikir yang memungkinkan otak mereka untuk mengenali, mengetahui, memahami, dan menalar sehingga mereka dapat lebih mudah memahami materi. Namun pada anak berkebutuhan khusus tentu terdapat sedikit perbedaan perkembangan kognitif dengan anak-anak pada umumnya. Autisme adalah suatu kondisi di mana individu lebih tertarik pada dunia mereka sendiri dan cenderung tidak ingin berinteraksi sosial dengan orang-orang di sekitarnya. Penelitian ini bertujuan untuk mengumpulkan informasi tentang gambaran perkembangan kognitif anak autis usia 6 tahun. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan sampel berupa satu anak autis yang bersekolah di TK “X” Kota Cirebon. Data penelitian diperoleh dari hasil observasi dan wawancara. Hasil penelitian menunjukkan bahwa perkembangan kognitif anak autism memang lebih kurang dibandingkan dengan anak-anak lainnya. Perkembangan kognitif anak autis usia 6 tahun berbeda, terutama dalam cara mereka belajar, berpikir, dan memecahkan masalah. Maka dari itu diperlukan intervensi dini sangat penting yang harus dilakukan oleh orang tua dan guru. Oleh karena itu, penting bagi orang tua dan guru untuk menciptakan lingkungan belajar yang mendukung dan sesuai dengan kebutuhan anak.